2012
DOI: 10.1016/j.drugalcdep.2011.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of substance use and psychological distress over the life course among a cohort of urban African Americans

Abstract: Background Substance use and psychological problems are major public health issues because of their high prevalence, co-occurrence, clustering in socio-economically disadvantaged groups, and serious consequences. However, their interrelationship over time is not well understood. Methods This study identifies and compares the developmental epidemiology from age 6 to 42 of substance use and psychological distress in a population of African American men and women. Data come from the Woodlawn Study, a longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 95 publications
3
41
0
3
Order By: Relevance
“…28 But, a similar longitudinal study of African American children followed into adulthood found substance use in adolescence predicted psychological distress in adulthood only for males. 29 In the prior study including Puerto Rican women, the women with increasing use frequency were also more likely to have a substance use disorder in adulthood. 28 This indicates the underlying mechanism here may be substance dependence or abuse, signaled by a persistent pattern of substance use across development, rather than increased interpersonal stress from risk behavior.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…28 But, a similar longitudinal study of African American children followed into adulthood found substance use in adolescence predicted psychological distress in adulthood only for males. 29 In the prior study including Puerto Rican women, the women with increasing use frequency were also more likely to have a substance use disorder in adulthood. 28 This indicates the underlying mechanism here may be substance dependence or abuse, signaled by a persistent pattern of substance use across development, rather than increased interpersonal stress from risk behavior.…”
Section: Discussionmentioning
confidence: 92%
“…A longitudinal survey following over 1,000 African Americans from age six to 42 found increased alcohol or marijuana use in adolescence predicted psychological distress in young adulthood but only for males. 29 By comparison, a study found substance use and sexual risk behavior in adolescence predicted depression in emerging adulthood, especially for females. 19 …”
mentioning
confidence: 99%
“…Findings are consistent with prior evidence that by mid-adolescence, internalizing symptoms, such as depression, are more prevalent among females when compared to males (Wade et al, 2002) and more strongly related to drug use (in particular for light/moderate levels of use; Waller et al, 2006). Depressive symptoms may contribute to initiation and continuation of drug use among females as a means to self-medicate in the face of negative affect (Green et al, 2012). Although a prospective, longitudinal design is necessary to ascertain developmental changes in this group, findings also suggest that there may be unique developmental correlates of drug use for males versus females depending on age.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal analyses for over 1,000 New Zealand youth indicated the best-fitting causal model was from alcohol abuse or dependence to depression, though they tested both directions (Fergusson, Boden, & Horwood, 2009). A longitudinal study of African Americans from age 6 to 42 found increased substance use (alcohol, marijuana, cocaine) in adolescence predicted psychological distress in young adulthood but only for men (Green, Zebrak, Robertson, Fothergill, & Ensminger, 2012). These latter findings conflict with other theoretical and empirical findings indicating females are more vulnerable to increased depression resulting from substance use, perhaps due to their greater interpersonal sensitivity and vulnerability to interpersonal stress (Ge, Lorenz, Conger, & et.…”
Section: Introductionmentioning
confidence: 99%